Terroir Products in North America: Dreams or Future Reality? - Lemasson, Jean-Pierre; Trubek, Amy (Cuizine, 2010)
This introduction seeks to analyze the French concept of terroir and its possible applications in North America. By focusing on Quebec and Vermont, respectively the most advanced Canadian province and American state in terms of defining and regulating terroir, it outlines the primary challenges in developing government certifications for terroir and explores ways in which the practical and legal considerations associated with such certifications compare and contrast with similar considerations in Europe. In so doing it focuses on three products: cheese, wine, and maple syrup.